A large multi-country outbreak of monkeypox across 41 countries in the WHO European Region, 7 March to 23 August 2022 - Vaughan, Aisling M; Cenciarelli, Orlando; Colombe, Soledad; Alves de Sousa, Luís; Fischer, Natalie; Gossner, Celine M; Pires, Jeff; Scardina, Giuditta; Aspelund, Gudrun; Avercenko, Margarita; Bengtsson, Sara; Blomquist, Paula; et al. (Euro surveillance, 2022)
Following the report of a non-travel-associated cluster of monkeypox cases by the United Kingdom in May 2022, 41 countries across the WHO European Region have reported 21,098 cases and two deaths by 23 August 2022. Nowcasting suggests a plateauing in case notifications. Most cases (97%) are MSM, with atypical rash-illness presentation. Spread is mainly through close contact during sexual activities. Few cases are reported among women and children. Targeted interventions of at-risk groups are needed to stop further transmission.
Keywords: Animals; Female; dítě; ženské pohlaví; outbreak; MPX; lidé; opičí neštovice; Monkeypox; World Health Organization; Mpox, Monkeypox; Exanthema; virus opičích neštovic; orthopoxvirus; Světová zdravotnická organizace; European Region; Disease Outbreaks; Monkeypox virus; exantém; Child; epidemický výskyt choroby; zvířata; Humans